LETTING STUDENTS MAKE MISTAKES LEADS TO SUCCES IN TEACHING ENGLISH - Shosura Khusenova Toshtemir qizi (Research Focus International Scientific Journal, 2023)
It might be difficult to teach children a new language, but it gets considerably more difficult when teachers try to totally avoid making mistakes. A tight and controlled learning environment is frequently brought about by the fear of making mistakes, which can impede students’ development and constrict their creativity. On the other hand, allowing students to make mistakes is a good strategy to encourage self-correction, critical thinking, and language confidence. Without some degree of trial and error, pupils may find it difficult to learn English because it is a complex language with many rules and exceptions. Teachers can assist students in overcoming their concerns and improving their language abilities by creating a safe, encouraging environment where it is acceptable to make mistakes. In this article, we will discuss the advantages of allowing students to make mistakes when teaching English and offer useful tactics that teachers can employ to motivate students to take calculated chances and learn from their failures. We will also go over the value of giving students constructive criticism and encouragement as well as how teachers can strike the perfect balance between correcting errors and letting students learn from them.